2011
DOI: 10.1016/j.visres.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement guidance in Chinese reading: Is there a preferred viewing location?

Abstract: In this study, we examined eye movement guidance in Chinese reading. We embedded either a 2-character word or a 4-character word in the same sentence frame, and observed the eye movements of Chinese readers when they read these sentences. We found that when all saccades into the target words were considered that readers eyes tended to land near the beginning of the word. However, we also found that Chinese readers’ eyes landed at the center of words when they made only a single fixation on a word, and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
199
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(239 citation statements)
references
References 30 publications
37
199
2
Order By: Relevance
“…In particular targeting saccades to the middle of words (Rayner, 1979) likely produced the word length effect. Also, since high frequency words are easier to process than low frequency words, more word skipping for high frequency words (Li, Liu & Rayner, 2011), and still others have suggested that, in fact, a multitude of factors might contribute to the decision of where to move the eyes in the upcoming text in Chinese (Zang, Liang, Bai, Yan & Liversedge, 2012). Clearly, this is area of eye movement control in Chinese reading that still requires extensive research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular targeting saccades to the middle of words (Rayner, 1979) likely produced the word length effect. Also, since high frequency words are easier to process than low frequency words, more word skipping for high frequency words (Li, Liu & Rayner, 2011), and still others have suggested that, in fact, a multitude of factors might contribute to the decision of where to move the eyes in the upcoming text in Chinese (Zang, Liang, Bai, Yan & Liversedge, 2012). Clearly, this is area of eye movement control in Chinese reading that still requires extensive research.…”
Section: Discussionmentioning
confidence: 99%
“…A final characteristic of Chinese that makes it visually distinct from Finnish and English, is that Chinese is an unspaced language, that is, there are no spaces between the words in Chinese sentences. The lack of word spacing in character-based languages has been shown to be very important in relation to eye movements, saccadic targeting and reading (see Bai, Yan, Liversedge, Zang, & Rayner, 2008;Blythe, Liang, Zang, Wang, Yan, Bai & Liversedge, 2012;Li, Liu & Rayner, 2011;Sainio, Hyönä, Bingushi & Bertram, 2007;Shen, Liversedge, Tian, Zang, Cui, Bai, Yan, & Rayner, 2012;Yan, Kliegl, Richter, Nuthmann & Shu, 2010;Zang, Liang, Bai, Yan & Liversedge, 2012). The lack of spaces between words in Chinese contributes further to its reduced horizontal extent, and this also means that a process of word segmentation is required for word identification to occur that is unnecessary in English and Finnish (with the exception of long, multimorphemic compound words, Bertram, Pollatsek, & Hyönä, 2004).…”
Section: ! 8!mentioning
confidence: 99%
“…However, research on this topic has been conducted primarily in languages based on the Latin alphabet (e.g., English, French, German), and, while recent research has examined non-alphabetic languages like Chinese (e.g., Li, Liu, & Rayner 2011), little is known about eye movements for alphabetic languages with fundamentally different visual characteristics. Arabic is the second-most widely read alphabetic language (after English) across the globe, yet few studies have examined eye movements when reading Arabic (e.g., Roman & Pavard, 1987;Roman, Pavard, & Asseleh, 1985) and, with the exception of a recent investigation of the perceptual span (Jordan, Almabruk, et al, 2014), have not examined fundamental visual influences on eye movement control.…”
mentioning
confidence: 99%
“…Second, Li and Pollatsek (2011) found that processing at the word level can feed back to low-level judgments, such as where a character is. Third, some eye movement measures in Chinese reading, such as fixation time and saccade length, are affected by word properties such as word frequency (Yan, Tian, Bai, & Rayner, 2006), predictability (Rayner, Li, Juhasz, & Yan, 2005), and length (Li, Liu, & Rayner, 2011). Fourth, a recent study (Li, Gu, Liu, & Rayner, 2012) has provided evidence that interrupting Chinese readers from simultaneously viewing two characters belonging to a word slows down their reading, as compared with when they can see both characters simultaneously.…”
mentioning
confidence: 99%